DIGITAL MARKETING STRATEGIES OF MSMES THROUGH THE UTILIZATION OF GOOGLE MAPS - Intan Putri; Diah Triesia; Feiza Salsabila Deka; Annisa Ghina Istigharany; Prima Sunami (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study investigated the utilization of Google Maps as a digital marketing strategy for micro, small, and medium enterprises (MSMEs), with a particular focus on Rumah Lapar in Palembang. The problem addressed in this research was the limited understanding of how digital platforms, especially Google Maps, could enhance business visibility, customer trust, and competitiveness in the digital era. This study was important because MSMEs often face barriers in adopting digital marketing strategies due to limited resources and digital literacy. A qualitative research method was employed using interviews, observations, and documentation as primary data collection techniques. The analysis was conducted through data reduction, data display, and conclusion drawing to ensure a comprehend sive interpretation of findings. The results showed that Google Maps significantly improved customer accessibility to business information, increased consumer trust through reviews and photos, and strengthened the professional image of the enterprise. Moreover, the utilization of the Insight feature enabled the business owner to monitor customer behavior and adjust marketing strategies accordingly. However, challenges such as inaccurate information, negative reviews, and limited digital literacy among MSMEs remained. The study concluded that Google Maps played a strategic role as a low-cost yet effective digital marketing tool, but its full potential could only be achieved through continuous updates, proactive engagement, and digital capacity-building programs. These findings highlighted the importance of integrating location-based marketing tools into the broader digital transformation strategy of MSMEs.